2016
DOI: 10.1515/jwld-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in modelling of water quantity and quality in two contrasting meso-scale catchments in Poland

Abstract: For citation: Marcinkowski P., Piniewski M., Kardel I., Srinivasan R., Okruszko T. 2016. Challenges in modelling of water quantity and quality in two contrasting meso-scale catchments in Poland. Journal of Water and Land Development. No. 31 p. 97-111. DOI: 10.1515/jwld-2016. AbstractThis study presents an application of the SWAT model (Soil and Water Assessment Tool) in two meso--scale catchments in Poland (Upper Narew and Barycz), contrasting in terms of human pressures on water quantity and quality. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…In this study, we build upon the existing, extensively calibrated and validated SWAT models of the Barycz and the Upper Narew catchments [35]. While the full description of model setup, calibration and validation was presented in the latter study, here we provide a brief overview, important in the context of the main goal of the present paper.…”
Section: Modelling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we build upon the existing, extensively calibrated and validated SWAT models of the Barycz and the Upper Narew catchments [35]. While the full description of model setup, calibration and validation was presented in the latter study, here we provide a brief overview, important in the context of the main goal of the present paper.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Marcinkowski et al [35] reported variable values of goodness-of-fit measures across different gauges and variables. For discharge, simulations were assessed as good (median KGE above 0.7 in both catchments).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The modelling of filtration process is difficult due to influence of various factors [MARCINKOWSKI et al 2016;MIODUSZEWSKI et al 2014;SCHALLER et al 2006]. For example, the mechanism in ultrafiltration (UF) is not clearly explained mainly because of the diversity of its application in different arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such models are MIKE SHE (Refsgaard & Storm 1995), SHET-RAN (Ewen et al 2000), TOPMODEL (Beven et al 1984), HBV (Lindström et al 1997) and SWAT (Neitsch et al 2002). The SWAT and HYPE models visualize the circulation of water and nutrients (nitrogen and phosphorus) starting from the catchment scale up to the continental scale (Abbaspour et al 2015, Donnelly et al 2014, 2016, Marcinkowski et al 2016, Piniewski 2016, Sitek & Ulańczyk 2016.…”
Section: Introductionmentioning
confidence: 99%